Respon Pertumbuhan Tanaman Rotala Rotundifolia (Buch.-ham. Ex roxb.) dengan Pemanfaatan Pupuk Organik Cair (POC) Hepagro - Ezward, Chairil; Ralan, Juher; Wahyudi, Wahyudi (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
Aquascape is the art of arranging water plants, rocks, sand, coral and ornamental fish placed in an aquarium to give the effect of gardening in water. Rotala rotundifolia (Buch.-Ham. ex Roxb.) Koehne is a member of the Lythraceae family and is an aquatic plant. Hepagro Liquid Organic Fertilizer (POC) is a liquid fertilizer resulting from the fermentation of microorganisms made from industrial liquid waste based on the Hepagro POC nutrient content Carbon (C), Phosphorus (P), Nitrogen (N), Potassium (K), Calcium (Ca) and Magnesium (Mg). This research aims to determine the response of Hepagro liquid organic fertilizer (POC) to the growth of Rotala rotundifolia (Buch.-Ham. ex Roxb.) plants. The research design used was a Non Factorial Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, consisting of P0 (No Hepagro Fertilizer), P1 (12.5 ml/l Hepagro Fertilizer), P2 (25 ml/l Hepagro Fertilizer). l) and P3 (Hepagro Fertilizer 37.5 ml/l). Based on the research results, giving Hepgro POC treatment had a real influence on all observation parameters with the best treatment being P3 37.5 ml/l with a plant height of 16.17 cm, stem diameter of 1.68 mm, root length of 1.43 cm and fresh weight. plant 0.60 grams.